Manufacturing and Development of Thai Sweet Sauce (Nam Pla Wan) - คำวชิระพิทักษ์ ผู้ช่วยศาสตราจารย์ ดร.มนัญญา; เสือโพธิ์ไทย กาญจนา; ทับกลาง อารีรัตน์ (Journal of Food Health and Bioenvironmental Science, 2017)
This research aimed to develop a standard recipe of Nam Pla Wan, a Thai sweet sauce. Three recipes from commercial formula1, commercial formula2 and commercial formula3 were evaluated for sensory characteristics (n=20, 9-point Hedonic scale) and the most favorably rated were selected. The commercial formula3 (control) served as a comparison formula for S1 formula and S2 formulas. Sensory quality scores from panelists for S1 Nam Pla Wan formula were: appearance (7.90), color (7.66), sweet (7.68), spicy (7.71), viscosity (7.93), and overall acceptance (8.00); however odor was not different from commercial formula3 and S2 (P≥.05). The average rating scores, categorized as the accepted treatment (formula), were in the range of 7.53 to 8.00 with color values of L * (41.20), a * (1.50) and b * (3.83). The S1 formula had a more firm consistency but was less cohesive and viscous; its aw was equal to 0.74 and contained 282.63 kcal per 100 g. The S1 Nam Pla Wan formula met the established industry standards for microbial safety.